Pelatihan Pengembangan Hard Skill Videografi Di SMK Negeri Wonosalam Guna Meningkatkan Promosi Desa Wisata - Gerialdi Robias Tsalatsa; Karsten Joshua Siahaan; Kharisa Imandina; Syadwina Daniar (Jurnal Masyarakat Mengabdi Nusantara, 2023)
Videography training is one of the steps to increase knowledge about videography because it cannot be denied, the need for videography is currently increasing in society. This videography training was held at Wonosalam State Vocational School with an audience of grade 10 students. The purpose of this videography training is as a forum for developing hard skills, giving students opportunities to be more creative, innovative, and expressive in making videography, and is expected to be able to develop skills in branding major. The method used in this activity was training by providing material on video shooting and video editing techniques as well as holding a videography competition for Wonosalam State Vocational High School students with the theme "Beautiful Wonosalam". The impact obtained is an increase in the knowledge of Wonosalam State Vocational School students regarding videography, and videography competitions are expected to be used as a way to explore the existing tourism potential in Wonosalam Village so that it is better known to the wider community.